The Influence of Public Service Advertisements on the Intentions to Eat Fish in Toddlers in Indonesia - Muhammad, Fasya Mazaya Sidqi; Zunaidi, Rizqa Amelia (Peneliti.net, 2024)
Public Service Announcements (PSAs) are one of the most widely used forms of promotion by the government to encourage the public to change their habits. The Ministry of Maritime Affairs and Fisheries has a program to raise public awareness about the importance of fish consumption for nutrition. This study examines the influence of the Gemarikan public service announcement on the intention to eat fish for stunting prevention. The focus of this research is to investigate the role of individual attention, information surveillance, elaboration, precautionary behavior towards stunting, and demographic features (such as occupation and age group). The method used in this study is Structural Equation Modeling (SEM), a multivariate analysis technique that aims to test the relationships between variables within a model. The findings indicate that attention, information surveillance, and elaboration are related to PSAs. Additionally, attention and information surveillance don't have a significant impact on precautionary behavior towards stunting, whereas elaboration is related to precautionary behavior towards stunting.